2014
DOI: 10.1021/je400253e
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–Liquid Phase Behavior of Solutions of 1,3-Dimethylimidazolium- and 1-Methyl-3-propylimidazolium Bis((trifluoromethyl)sulphonyl)amide (C1,3mimNTf2) in n-Alkyl Alcohols

Abstract: The phase behavior of binary liquid mixtures of the ionic liquids (ILs) 1,3dimethylimidazolium bis((trifluoromethyl) sulfonyl) amide (C 1 mimNTf 2 ) and 1-methyl-3propyl imidazolium bis ((trifluoromethyl) sulfonyl) amide (C 3 mimNTf 2 ) with n-alkyl alcohols (C n OH; 3 ≤ n ≤ 8) was investigated. The phase diagrams are obtained by applying the cloud-point method on a set of synthetically prepared samples. Partial miscibility with an upper critical solution temperature (UCST) was observed. The study focuses on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
80
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(96 citation statements)
references
References 33 publications
12
80
2
Order By: Relevance
“…In particular, the name, the molecular formula, the abbreviation, the CAS identifier, the purity, the drying method, and the water content are given. The samples were used as received with the exception of drying (using molecular sieves in the case of alcohols and vacuum drying in the case of ionic liquids); a detailed description of the drying steps was given elsewhere. , The absence of halides as relevant impurities, which may hamper the phase behavior of the IL mixtures, was confirmed by a test with silver nitrate solutions. The existence of traces of potential residues of the synthesis of the ILs was excluded by a careful and repeated cross check of the loci of the critical demixing temperatures of different IL solutions prepared from different batches of the IL; the results were compared to known results from prior works. They show the scatter within the desired level of uncertainty; no systematic shifts were found.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, the name, the molecular formula, the abbreviation, the CAS identifier, the purity, the drying method, and the water content are given. The samples were used as received with the exception of drying (using molecular sieves in the case of alcohols and vacuum drying in the case of ionic liquids); a detailed description of the drying steps was given elsewhere. , The absence of halides as relevant impurities, which may hamper the phase behavior of the IL mixtures, was confirmed by a test with silver nitrate solutions. The existence of traces of potential residues of the synthesis of the ILs was excluded by a careful and repeated cross check of the loci of the critical demixing temperatures of different IL solutions prepared from different batches of the IL; the results were compared to known results from prior works. They show the scatter within the desired level of uncertainty; no systematic shifts were found.…”
Section: Methodsmentioning
confidence: 99%
“…The phase diagrams were determined by applying the synthetic method. The preparation of the samples and the visual determination of the cloud point temperatures ( T cloud ) followed the standard procedures, which were optimized over the last years. Finally, samples of a typical size of about 0.7 g were prepared in PTFE-sealed Duran culture tubes (Duran Group, Mainz, Germany) under a protective argon atmosphere (Air Liquide, w = 0.99999) to avoid contact with air and humidity. The semiautomated procedure of sample preparation (for details, consider ref ) utilizes a gravimetric determination of the composition and provides an overall uncertainty in the mole fraction of each sample of U ( x IL ) = 2 × 10 –4 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…the chemical potential of solvent m 1 , the difference of chemical potential between solvent and solute Dm, the temperature T and the pressure P. Our previous investigations on binary systems of benzonitrile + n-alkane, dimethyl carbonate + n-alkane, and nitrobenzene + n-alkane showed that the complete scaling theory can well represent the experimental asymmetric behavior of the diameter of the coexistence curves. [24][25][26] Some investigations involving the application of the complete scaling theory to describe the asymmetric criticality of ionic solutions have been reported; 12,17,18,[27][28][29] however the contribution of the heat capacity in ionic solutions has been rarely considered, 12,17 which requires precise heat capacity data in both critical and non-critical regions.…”
Section: Introductionmentioning
confidence: 99%